2021
DOI: 10.21608/ejss.2021.61131.1432
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Land Suitability for Surface and Drip Irrigation Systems in the Northwestern Coast of Egypt.

Abstract: T HIS WORK aimed at the assessment of the land suitability for surface and drip irrigation systems in a part of west Matrouh area, northwestern coast of Egypt. For establishing this target, a digital elevation model (DEM) and SENTENAL-2 image were used for identifying the physiographic units of the studied area. The integration between satellite image and soil survey using Arc-GIS10.9 software was done to produce the different maps of this work. These properties were used for assessment the land suitability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Using the ALES arid-model in arid and semi-arid regions facilitated the finding of the most suitable agricultural system to be adopted (Abd El-Kawy et al, 2010). Land assessment applied to assess the land capacity and land suitability for a specific use in different conditions, can be performed automatically by using ALES software and GIS technique (Abdellatif et al, 2021 andGouda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using the ALES arid-model in arid and semi-arid regions facilitated the finding of the most suitable agricultural system to be adopted (Abd El-Kawy et al, 2010). Land assessment applied to assess the land capacity and land suitability for a specific use in different conditions, can be performed automatically by using ALES software and GIS technique (Abdellatif et al, 2021 andGouda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The aims of land evaluation are the identification of adverse effects and benefits of land uses (Mahmoud et al, 2020 andAbdel Rahman et al, 2017) Geographic Information System (GIS) can be used as an effective tool in many agricultural applications such as cropland assessment for sustainable agricultural land use planning (Aldabaa & Yousif,2020). Abdellatif (2021) carried out an evaluation of the application of surface and Drip irrigation in the Matrouh area, northwest coast of Egypt, the results indicated that the system of drip irrigation increased the suitability of land by 31% compared to surface irrigation. The most limiting factors were texture, profile depth, drainage condition, and the ratio of CaCO3 in profile.…”
Section: Introductionmentioning
confidence: 99%